Study of Ethnobotany Plants for Traditional Security Equipment Paberasan Village, Sumenep, Madura - Hamim, Jazuli Mohammad; Yunia, Asti Eka; Nur, Azizah, Naailatu; Putri Irsadul, Ummah Yunita; Sulisetijono, Sulisetijono (Proceeding International Conference on Global Resource Conservation, 2013)
Study of plants utilization by particular communities studied in the field of ethnobotany. One of the utilization of the plants since the first in Indonesia as traditional security equipments that are passed from generation to generation. Security is associated with the mystical and nonmistis security. Paberasan village, Sumenep Madura is one of the many villages where people still use plants as traditional security equipments. This study aims to determine which plants are used as traditional security tool that exist in the village Paberasan. The method used in this research is a method of participatory observation and interviews with respondents native village. Results from this study were analyzed using descriptive analysis, such as leaves of Artocarpus communis are used as a mosquito repellent. There are also other plants such as Cocos nucifera, Bambusa vulgaris and Phempis accidula.Keywords: Plants, Traditional security equipments, Paberasan SumenepÂ